The Effect of Urinary Catheters on Microbial Biofilms and Catheter Associated Urinary Tract Infections - Kirmusaoglu, Sahra; Yurdugül, Seyhun; Metin, Ahmet; Vehid, Suphi (Urology Journal, 2017)
Purpose: The aims of this study were to determine relationship between biofilm producer microorganisms attached to urinary catheters (UCs) and urinary catheter-associated urinary tract infections (CAUTIs), to determine the rate of CAUTI development and the relationship between CAUTI and catheterization period in catheterized patients. Materials and Methods: Urinary catheters from 143 inpatients who were hospitalized in Abant Izzet Baysal University Hospital Urinary Service, and urine samples of these patients before and after catheterization of urinary catheter were collected. Culture-based microbiological evaluation of urinary catheters removed from inpatient and urine samples collected from inpatients were performed before and after catheterization of urinary catheter to identify various organisms and determine biofilm production by them. Results: The incidence of CAUTIs was 13% (18/143) in catheterized inpatients. Biofilm producer microorganisms such as Escherichia coli (E. coli ), Klebsiella pneumoniae, Pseudomonas aeruginosa, Proteus mirabilis that were isolated from UCs removed from inpatients were found to cause CAUTI (P < .001). Conclusion: Incidence of CAUTIs is increased by the usage of UCs and prolonged catheterization period.